Luther's Works on CD-ROM: 55-volume american edition - Luther, Martin (Veröffentlichungen der Johannes-a-Lasco-Bibliothek Große Kirche Emden, 2002)
Martin Luther`s message of faith has never been more accessible and comprehensive. For the first time, all 55 volumes of the Luther corpus are available on CD-ROM. Convenient and fully searchable, this resource is indispensable for preachers and readers of Luther. Note-taking, bookmarking, and highlighting features abound.